Оценка баланса кортизол/инсулин у беременных с различным уровнем тревожности - Сюсюка, В. Г.; Сюсюка, Володимир Григорович; Syusyuka, V. G. (Агентство Орбіта-ЮГ, 2015)
Стрессовые воздействия пережитые матерью во время беременности, включая интенсивную тре- вогу, депрессию, прием глюкокортикоидов, могут приводить к снижению веса и размеров тела плода при рождении, снижению размеров гиппокампа, клеточным нарушениям в мозге. Повышение в кро- ви матери концентрации основного гормона стресса (кортизола) может приводить к недостаточности разрушающего его фермента в плаценте и материнский кортизол может попадать в кровь плода. Стресові впливи пережиті матір'ю під час вагітності, включаючи інтенсивну тривогу, депресію, прийом глюкокортикоїдів, можуть призводити до зниження ваги і розмірів тіла плода при народженні, зниження розмірів гіпокампу, клітинних порушень у мозку. Підвищення в крові матері концентрації основного гормону стресу (кортизолу) може призводити до недостатності руйнуючого його ферменту в плаценті і материнський кортизол може потрапляти в кров плода. Now it is proved that mental life of prenatal developing baby is active and mainly depends on emotions and feelings of the mother and the most important thing is that it is the foundation of psychoemotional characteristics of the baby for many future years. Prenatal negative effects have the strongest destructive influence. If during pregnancy mother had severe stress, intensive anxiety or depression or took glucocorticoids this could lead to reduction of weight and body size of fetus by delivery, decrease of hippocampus size and cellular damages in the brain. Increase of concentration of the main stress hormone (cortisol) in the mother’s blood leads to enzyme destroying it in placenta can not cope anymore with stress and mother’s cortisol comes into blood of fetus. Artificially created stress condition is occured.
Оцінка балансу кортизол/інсулін у вагітних з різним рівнем тривожності
Estimation of cortisol/insulin balance of pregnant women with different level of anxiety
Keywords: беременность; психоэмоциональное состояние; тревожность; гормоны; кортизол; инсулин; вагітність; психоемоційний стан; тривожність; гормони; кортизол; інсулін; pregnancy; psychoemotional state; anxiety; hormones; cortisol; insulin